The Use of Coffee Cherry Pulp Extract as an Alternative to an Antibiotic Growth Promoter in Broiler Diets - Wanaporn Tapingkae; Phatchari Srinual; Pimporn Khamtavee; Naret Pintalerd; Thanongsak Chaiyaso; Mongkol Yachai; Chanidapha Kanmanee; Chompunut Lumsangkul; Orranee Srinual (Animals)
Coffee cherry pulp (CCP) is a by-product of coffee bean production. CCP contains amounts of phenolic compounds that are beneficial for animals. This study evaluated the impact of coffee cherry pulp extract (CCPE) supplementation on growth performance, meat quality, carcass characteristics, serum biochemistry, cecum microbial population, intestinal morphology, and immune and antioxidant responses of broilers. Five hundred 1-day-old Ross 308 chicks were randomly assigned to five groups: a basal diet control, a basal diet with antibiotic growth promoters at 0.25 g/kg, and groups supplemented with CCPE at 0.5, 1.0, and 2.0 g/kg diet over 35 days. The results showed that throughout the experimental period, the groups supplemented with CCPE improved their final weight, average daily gain, and feed conversion ratio (p < 0.05). CCPE at 1.0 and 2.0 g/kg diet reduced the average daily feed intake (p < 0.05). In addition, CCPE at 0.5 g/kg reduced levels of serum alanine transaminase and aspartate aminotransferase (p < 0.05). Triglyceride levels were the lowest in CCPE 2.0 (p < 0.05). In the group supplemented with CCPE at all levels, the high-density lipoprotein levels significantly increased (p < 0.05). Drip loss in the breast at 24 and 48 h decreased (p < 0.05). Additionally, live weight, defeathered weight, and carcass weight significantly increased (p < 0.05). Furthermore, CCPE improved intestinal morphology, especially villus height and the villus height per crypt depth ratio (p < 0.05). CCPE supplementation also reduced pathogenic bacteria, increased Lactobacillus spp. (p < 0.05), and increased the expression of immune-related genes and antioxidant activity in the liver and intestines (p < 0.05). Therefore, the use of CCPE as an alternative to antibiotics in broiler feed improved growth performance and health parameters in broilers. It provides a sustainable and environmentally friendly option for supplementary feed, contributing to more efficient poultry nutrition management.